Comprehensive Evaluation of Starch and Noodles Quality of Different Sweet Potato Varieties Based on Principal Component Analysis and Cluster Analysis - Mi LUO; Wang YIN; Renju DENG; Yufang GUAN; Mu PAN; Qiaoyu WU; Mei FU (Shipin gongye ke-ji)
To scientifically evaluate the starch quality of different sweet potato varieties and establish the sweet potato starch quality evaluation system, 10 starchy sweet potato varieties were used as experimental materials. Their starch composition, particle size, molecular polymerization, thermodynamic characteristics, gelatinization properties, and noodles quality indexes were determined and analyzed. The differences in starch properties among different sweet potato varieties were thoroughly investigated. Furthermore, the quality of starch was evaluated using correlation analysis, principal component analysis (PCA), and cluster analysis. Results exhibited significant variations in starch quality indexes among different varieties (P<0.05). Correlation analysis revealed varying degrees of association among the starch property indexes, with noodles quality primarily influenced by starch composition, particle size and molecular polymerization. By principal component analysis, 28 quality indicators were simplified into 7 principal components, and the cumulative variance contribution rate was 96.761%, which could reflect most of the information of the original indicators. The comprehensive scores of starch quality indexes of 10 sweet potato varieties were ranked as Yushu 198, Shangshu 19, Yushu 50, Yushu 15, Qining 19, Qianshu 11, Xushu 22, Sushu 28, Xushu 37, Eshu 6. The 10 sweet potato varieties were classified into five categories through cluster analysis. Among them, Shangshu 19 in the third category exhibits larger starch particle size and higher setback value, a low noodles breaking rate and excellent elasticity, which was suitable for noodle processing. Yushu 198 has the highest score, with better noodles mastication, but higher cooking loss and greater hardness. Eshu 6, Sushu 28 and Xushu 37 received low comprehensive scores indicating poor noodles quality and unsuitability for noodles processing.